Benign Prostatic Hyperplasia : Conservative and Operative Management - Jakse, G. (Gerhard) (Springer Berlin Heidelberg, 1992)
The treatment of benign prostatic hyperplasia (BPH) has considerably changedin the past few years. New treatment options are now available such as stents, hyperthermia or antiandrogens. The indication for these new treatment modalities has still to be defined. Some of these may be of help in poor risk patients, others may improve symptoms without majorimport on the underlying disease. Transurethral resection of the prostate (TURP) and open surgical procedures are still the cornerstones of the treatment in patients with significant bladder outlet obstruction. However, further improvements in technique are warrented to minimize mortality.